Microplastics in soils: an environmental geotechnics perspective - O'Kelly, Brendan; Xiao, Liwen; Wang, Jing; Li, Dunzhu (My University, 2021)
Microplastics (MPs) are emerging persistent contaminants in the terrestrial subsurface, and evidence has emerged for significant effects of MPs on the biological and ecosystem functions of soils. Main MP sources include land spreading of sewage sludge and biowaste composts, plastic mulching film used in horticultural fields, waste water irrigation and leachate from the landfills, among others. This updated state-of-the-art review paper describes recent experimental and numerical research and developments in understanding the accumulation and fate and effects of MPs in the soil environment (focusing on their storage, degradation, transportation, leaching to groundwater etc.), followed by mitigation and bioremediation measures, including MP-eating soil bacteria and fungi and the best management practices for reducing MP pollution of soil. Other areas covered are the combined effects of MPs and various other environmental contaminants (heavy metals, organic pollutants and antibiotics) in soil ecosystems and the standardisation of methods for detection, quantification and characterisation of MPs in soils, which is critical for MP research. The paper concludes by identifying knowledge gaps and presents recommendations on prioritised research needs.
PUBLISHED
This paper was the third most read article, and eighth most downloaded paper, of 2022 across all journal titles published by ICE Publishing. It was featured in a news article published by The Conversation and syndicated by at least four other news outlets.
Keywords: Land contamination; Pollution; Waste management & disposal; Nanoscience & Materials; Smart & Sustainable Planet; ATR FTIR SPECTROSCOPY; BIOREMEDIATION; Biodegradation; CHANGING ECOSYSTEM; ECOSYSTEMS; Environmental Geotechnics; FTIR SPECTROSCOPY; Geotechnics; HEAVY-METALS; Microplastic; POLYMER DEGRADATION-CONTROLLED RELEASE; SEM; SEWAGE SLUDGE; SOILS; TERRESTRIAL ECOSYSTEMS; TILLAGE SOILS; emerging organic contaminants; nanoplastic